2001
DOI: 10.1159/000052922
|View full text |Cite
|
Sign up to set email alerts
|

Pudendal Nerve Terminal Motor Latency in Women with Genuine Stress Incontinence and Prolapse

Abstract: The aim of this study was to investigate changes in pudendal nerve terminal motor latency (PNTML) time in women with genuine stress incontinence (GSI) and with or without prolapse, in conjunction with measurement of maximal urethral closure pressure (MUCP). Eighty-five patients participated in the study and they were allocated to one of four groups, including the control group. A statistically significant difference was found in the PNTML time between patients with GSI and patients of the control group. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 16 publications
(19 reference statements)
0
8
0
Order By: Relevance
“…Increased PF activity has previously been reported in a subgroup of women with incontinence, 5,38 and may represent a compensation mechanism to control, or moderate, symptoms. 24 Although, maximal urethral closure pressure has been shown to be decreased in women with incontinence, 39,40 the effect of PF activity on urethral closure at rest 8 and during functional tasks is unclear.…”
Section: Muscle Activity In Continent and Incontinent Womenmentioning
confidence: 99%
“…Increased PF activity has previously been reported in a subgroup of women with incontinence, 5,38 and may represent a compensation mechanism to control, or moderate, symptoms. 24 Although, maximal urethral closure pressure has been shown to be decreased in women with incontinence, 39,40 the effect of PF activity on urethral closure at rest 8 and during functional tasks is unclear.…”
Section: Muscle Activity In Continent and Incontinent Womenmentioning
confidence: 99%
“…This approach owes its popularity to a number of studies reporting prolonged TMLs in various anorectal disorders, 101,121 such as fecal incontinence, 18,48,58,62,94,120,129,130,142,150,162,166 obstetrical lesions, 141,144,146,152,153,155 perineal descent, 6,51,53,62,77,143 or even constipation. 162,163 Evidence of pudendal/ anal neuropathy, as shown by a prolonged TML, was proposed as a predictive factor for the clinical outcome of biofeedback therapy 67 or surgical repair 13,39,145 of pelvic floor disturbances, even in case of unilateral neuropathy.…”
Section: Terminal Motor Latency Measurementmentioning
confidence: 99%
“…delancey (11) proposed that Pn injury causes denervation of pelvic floor muscles. Previous studies of pelvic floor electromyography of patients with SUI, nerve conduction velocity, pelvic floor muscle pathology and neurofibrillary immunohistochemical staining have also demonstrated that pelvic denervation is present in patients with Sui (9,30,31).…”
Section: Discussionmentioning
confidence: 91%